Irreconcilable judgments in the EU Regulations: Reforming the ground(s) for refusal of enforcement - Tičić, Martina (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Despite the fact that the abolition of exequatur seems to have become the norm under the EU regulations dealing with monetary claims, all of the regulations that fall under this category still preserve some grounds for refusal of enforcement of judgments. One of the refusal grounds which remained, even in the regulations which otherwise abolished all possibility of refusal, is the ground of irreconcilability with another judgment. Despite its importance, this refusal ground can sometimes still be quite complex to interpret. This paper thus analyses the notion of ‘irreconcilable judgments’, clarifying the remaining difficulties in interpretation. Moreover, it compares the diverging solutions offered in different regulations, and ultimately proposes a potential reform.
Keywords: Irreconcilable judgments; refusal of enforcement; Brussels I Recast; second-generation instruments; private international law